Graves Disease Following the SARS-CoV-2 Vaccine: Case Series. (December 2021) - Weintraub, Michael A.; Ameer, Barbara; Sinha Gregory, Naina
Widespread vaccination is a principal strategy to mitigate the spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and lessen the global burden of coronavirus disease 2019 (COVID-19). Information is rapidly evolving about the impact of SARS-CoV-2 vaccines on the immune and endocrine systems. This case series heightens clinical awareness of possible thyroid effects and conveys knowledge of what to monitor, which are fundamental components of public health and pharmacovigilance. We present a case series of Graves disease following mRNA SARS-CoV-2 vaccination, with symptoms and altered thyroid function tests developing within 7 days of the first dose in 2 women aged 38 and 63 years, and 28 days after the second dose in a 30-year-old man. New-onset Graves disease occurred following administration of mRNA vaccines against SARS-CoV-2. Based on the timing of signs and symptoms relative to administration of the vaccine and the absence of other probable causes, we consider the vaccine as a potential contributor to the diagnosis. The viral spike protein, delivered indirectly through an encoded mRNA vaccine, may be capable of triggering an inflammatory cascade and immune response triggering thyroid dysfunction.